2011
DOI: 10.1111/j.1365-2133.2010.10098.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparative study of tolerance and satisfaction in the treatment of actinic keratosis of the face and scalp between 5% imiquimod cream and photodynamic therapy with methyl aminolaevulinate

Abstract: Both PDT and imiquimod are treatments that are generally well tolerated. While both treatments provide a high level of satisfaction, PDT appears to be slightly superior in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Therefore, PDT continues to be valued in terms of satisfaction, as reported in the literature. 5,8,14,18,19 Furthermore, more patients treated with PDT showed good tolerance to treatment (37.5% PDT vs 24% imiquimod) and a lower percentage of patients showed poor tolerance to treatment (35% PDT vs 43% imiquimod) versus those taking imiquimod, although the differences were not statistically significant. This could be a result of the shorter duration of treatment and discomfort with PDT versus imiquimod, which must be applied over a 4-week period.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, PDT continues to be valued in terms of satisfaction, as reported in the literature. 5,8,14,18,19 Furthermore, more patients treated with PDT showed good tolerance to treatment (37.5% PDT vs 24% imiquimod) and a lower percentage of patients showed poor tolerance to treatment (35% PDT vs 43% imiquimod) versus those taking imiquimod, although the differences were not statistically significant. This could be a result of the shorter duration of treatment and discomfort with PDT versus imiquimod, which must be applied over a 4-week period.…”
Section: Discussionmentioning
confidence: 93%
“…In a recent randomized comparative study, we did not find differences in tolerance between PDT and imiquimod, although satisfaction was greater among patients receiving PDT than among those treated with imiquimod. 14 To our knowledge, this is the first study that has compared imiquimod 5% cream, methyl aminolevulinate PDT, and the sequential application of both.…”
mentioning
confidence: 97%
“…With regards to patient tolerance and satisfaction, when comparing imiquimod 5% to other therapies for AKs such as photodynamic therapy (PDT) with methyl aminolevulinate (MAL PDT), Serra-Guillen and colleagues found that both treatments are well-tolerated by patients, with no significant difference in tolerance found with regards to patient sex, race, sun-exposure time, or hair color. 27 There was a higher percentage of patients reporting "very satisfied" with treatment for MAL PDT compared to imiquimod (93% vs. 62%, P = 0.004); however, most patients reported that they would continue the same treatment. Economic studies have demonstrated that imiquimod may be the more cost-effective choice compared to MAL PDT.…”
Section: Dosing Regimen Commentsmentioning
confidence: 87%
“…To our knowledge, this is the first study assessing treatment satisfaction using a validated tool. One previous study used a 7-point Likert scale and another an analogue scale (0-10) [22,25]. …”
Section: Discussionmentioning
confidence: 99%